Low vision and the risk of dementia: a nationwide population-based cohort study - Jisun Paik; Minji Ha; Youn Hea Jung; Gee-Hyun Kim; Kyungdo Han; Hyun Seung Kim; Dong Hui Lim; Kyungsun Na (2020)
Abstract Recent studies suggested that an association exists between vision loss and cognitive impairment, although it is still vague whether there are causal relationships or direct association between low vision and dementia. We were to investigate the association between low vision and dementia in the Korean population using the National Health Insurance Service (NHIS) database. We analyzed the data of 6,029,657 subjects aged ≥40 years, drawn from Korea National Health Insurance Service. The hazard ratio (HRs) and 95% confidence interval (CIs) of dementia, Alzheimer’s disease (AD), and Vascular dementia (VD) were estimated using multivariable Cox proportional hazards regression models. Statistical analysis showed that subjects with more severe visual impairments have a higher risk of dementia, AD, and VD after adjusting for compounding variables. The HRs of dementia increased significantly as visual acuity worsened (HRs 1.444 [95% CIs 1.415–1.473] for visual acuity (VA) < 1.0, 1.734 [1.693–1.777] for VA < 0.3, 1.727 [1.686–1.770] for VA < 0.1 and 1.991[1.902–2.085] for visual loss). Baseline visual loss and visual impairment were positively associated with the risk of dementia, AD, and VD. From the results of this nationwide population-based cohort study, we suggest that there is a significant increase in the incidence of dementia in subjects with low vision.